Kif20a inhibition reduces migration and invasion of pancreatic cancer cells - Stangel, Daniela; Erkan, Mert; Buchholz, Malte; Gress, Thomas; Michalski, Christoph; Raulefs, Susanne; Friess, Helmut; Kleeff, Jörg H. (Journal of surgical research, 2015)
Backround - The Translational Genome Research Network in Pancreatic Cancer performed a meta-analysis of publicly available various high-throughput gene analysis panels to identify drugable targets. There, the most differentially expressed gene between normal and cancerous pancreas was Kif20a. The aim of the study was to verify this expression pattern and further characterize Kif20a in pancreatic cancer. - Materials and methods - Detailed expression analyses were carried out in pancreatic tissues and in a wide panel of pancreatic cells including ductal adenocarcinoma (PDAC) and neuroendocrine-cancer cell lines as well as immortalized human pancreatic ductal epithelial and primary stellate cells using quantitative real-time polymerase chain reaction, immunohistochemistry, immunofluorescence, and immunoblot analyses. Effects on proliferation, apoptosis, and cell cycle were assessed by MTT assays, caspase-cleavage assays, and fluorescence-activated cell sorting analysis after Kif20a silencing. Cell motility was assessed by migration and invasion assays as well as time-lapse microscopy. - Results - Mean Kif20a messenger RNA expression was 18.4-fold upregulated in PDAC tissues compared with that in the normal pancreas. In line, neuroendocrine-cancer cell lines display a 1.6-fold increase and ductal adenocarcinoma cell lines a 11-fold increase of Kif20a messenger RNA (P = 0.009) in comparison with primary stellate cells. A 7.3-fold overexpression was also found in immortalized pancreatic ductal epithelial cells. Kif20a silencing with small interfering RNA molecules resulted in an inhibition of proliferation, motility, and invasion of pancreatic cancer cell lines. - Conclusions - Targeting Kif20a reduces proliferation, migration, and invasion of pancreatic cancer cells. Together with its significant overexpression in PDAC, this makes it a potential target for diagnostic and interventional purposes.
Gesehen am 22.06.2020